(3h GdHQhajd GdfeGFi ddHhQJjL (B(PEP3) (3GdJTNjU GdaGQbi dHYV EYGbGJ Gdfeh GdTGed HGSJNOGe GdHQhajd GdfaSi GdJQHhi (B/ s - (3agOg HfJ YHOGdYRjR GdajUd s; {uFE8D}{uFEF4}{uFEE4}{uFE8E}{uFEE5} {uFEB4}{uFECC}{uFEF4}{uFEA9} {uFECB}{uFE92}{uFEA9}{uFE8D}{uFEDF}{uFEA4}{uFEE4}{uFEF4}{uFEA9}; {uFEA8}{uFE8E}{uFEDF}{uFEA9} {uFECB}{uFE92}{uFEA9}{uFE8D}{uFEDF}{uFEAD}{uFE8D}{uFEAF}{uFED5} {uFE8D}{uFEDF}(3fLG(B{u(3FEAD(B} : s ((3GdbGgQI (B: s {uFED3}{uFEEC}{uFEA9}{uFEE9} {uFE92}{uFEE8}{uFE95} {uFECB}{uFE92}{uFEA9}{uFE8D}{uFEDF}{uFECC}{uFEAF}{uFEF4}{uFEAF} {uFE8D}{uFEDF}{uFED4}{uFEF4}{uFEBC}(3d (B: s, 2016)
(3JgOa GdOQGSI Gdi (B{u(3FE8D(B}{u(3FEDF(B}{u(3FE98(B}{u(3FEA4(B}{u(3FED8(B}{u(3FED5(B} {u(3FEE4(B}{u(3FEE5(B} {u(3FED3(B}{u(3FE8E(B}{u(3FECB(B}{u(3FEE0(B}{u(3FEF4(B}{u(3FE94(B} {u(3FE8D(B}{u(3FEB4(B}{u(3FE98(B}{u(3FEA8(B}{u(3FEA9(B}{u(3FE8D(B}{u(3FEE1(B} {u(3FE8D(B}{u(3FEDF(B}{u(3FE92(B}{u(3FEAD(B}{u(3FEED(B}{u(3FED3(B}{u(3FEF4(B}(3d (B{u(3FE8D(B}{u(3FEDF(B}{u(3FEE8(B}{u(3FED4(B}{u(3FEB1(B} {u(3FE98(B}{u(3FEAD(B}{u(3FE92(B}{u(3FEED(B}(3i ai (B{u(3FE98(B}{u(3FEB8(B}{u(3FEA8(B}{u(3FEF4(B}{u(3FEB9(B} {u(3FEED(B} {u(3FE98(B}{u(3FED8(B}{u(3FEF4(B}(3`(B{u(3FEF4(B}{u(3FEE1(B} {u(3FEA4(B}(3`(B{u(3FE8E(B}{u(3FEFB(B} {u(3FE95(B} {u(3FE8D(B}{u(3FEF7(B}{u(3FEC1(B}{u(3FED4(B}{u(3FE8E(B}(3d (B{u(3FEE4(B}{u(3FEE5(B} {u(3FEAB(B}{u(3FEED(B}(3i (B{u(3FE87(B}{u(3FECB(B}{u(3FE8E(B}{u(3FED7(B}{u(3FE8E(B}{u(3FE95(B} {u(3FE8D(B}{u(3FEDF(B}{u(3FEE8(B}{u(3FEE4(B}{u(3FEED(B} {u(3FE8D(B}{u(3FEDF(B}{u(3FEB8(B}{u(3FE8E(B}{u(3FEE4(B}(3d(B. (3h JchfJ YjfI GdOQGSI ef (B(20) (3WadG ebSejf Gdi (B(10( (3CWaGd ef Phi GdPGJhjjf h (B(10) (3ef Phi GdESHQLQ GdedJMbjf HeDSSI QDjI ddJhMO h Phi GdGMJjGLGJ GdNGUI HefWbI THQG GdNjeI(B: (3HeMGaXI GdbdjhHjI(B: (3h GSJNOeJ GdHGMKI ebjGS LjdjGe dJbOjQ GdPGJhjI (B((3JQLeI h JYQjH(B: (3YGOd YHOGddg(B:2006): (3h ebjGS LjdjGe ddGSHQLQ (B((3JQLeI(B: (3eMeO YhOI(B:2012): (3h ebjGS Gdeda GdfaSi GdJQHhi (B((3Hi Gi Hi (B3) (2005(3SjThHdQ(B) ((3JQLeI(B: (3LeGd MejOGf(B:2008): (3h GdJbjje GdfeGFi dHQfGeL GdHhQJGL(B: (3h bO GTGQJ GdfJGFL Gdi hLhO aQhb Hjf eJhSWGJ QJH OQLGJ GdCWaGd GdPGJhjjf h eJhSWGJ QJH OQLGJ GdCWaGd GdPGJhjjf h GdCWaGd GdESHQLQ ceG jJVM Pdc ef NdGd GSJNOGe GdHQhajd GdfaSi GdJQHhi h GdHQhajd GdfeGFi dHQfGeL GdHhQJjL h Pdc ai egGQGJ (B((3GdJhGUd h GdMQcI h GdSdhcjGJ GdJcjajI h JbQjQ hdi GdCeQ h GdOQLI GdcdjI(B) (3YfO eSJhi (B(.01): (3HjfeG de jXgQhG aQhbG PGJ OdGdI GMUGFjI ai HYO GdegGQGJ GdMQcjI GdcHjQIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI ddWahdI GdeHcQI (B- (3bSe GdYdhe GdfaSjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3EYGbGJ Gdfeh GdTGed s; (3GdJTNjU GdaGQbis; (3GdYdhe GdfaSjI s